Implementasi Metode Rapid Application Development Dalam Pembangunan Sistem Penerimaan Kas Atas Penjualan - Nur Hidayati (LPPM Universitas Bina Sarana Informatika, 2018)
The cooperative is one of the pillars of the economy of Indonesia. This has supported a variety of facts and data that mention that Indonesia's economy is still dominated by sectors with low productivity, such as agriculture, trade and industry. There are also cooperative activities in sales, purchasing and processing of financial data. Activities related to the recording of incoming cash often known with the receipt of cash. Cash receipt data processing over the sale of the Koperasi Pegawai Republik Indonesia (KPRI) Usaha Sekerja BBalitvet Bogor is still done manually. This causes problems such as the delay in the making of reports each month. And the existing notes in the book could be lost because it could not be backed up. KPRI Usaha Sekerja BBalitvet Bogor is a co-operative which has great expectations in order for koperasinya to be more evolved than today. The need for the development of a system of manual systems into a computerized system for applied KPRI Usaha Sekerja BBalitvet Bogor. So that it can complete the nurturing faced at this time and can help the performance of the employee in performing the activities data processing data processing, particularly in the acceptance of cash over the sales. The author tried to give a recommendation in the form of the proposed design of the computerized system that is better than running at KPRI Usaha Sekerja BBalitvet Bogor by using the programming language Visual Basic.net. The method waterfall authors choose to help resolve existing problems on KPRI Usaha Sekerja BBalitvet Bogor